TORC1 Regulates Thermotolerance via Modulating Metabolic Rate and Antioxidant Capacity in Scallop Argopecten irradians irradians - Longfei Chu; Ancheng Liu; Jiaxi Chang; Junhao Zhang; Xiujiang Hou; Xinghai Zhu; Qiang Xing; Zhenmin Bao (Antioxidants)
Target of rapamycin complex 1 (TORC1) is a key regulator of metabolism in eukaryotes across multiple pathways. Although TORC1 has been extensively studied in vertebrates and some invertebrates, research on this complex in scallops is limited. In this study, we identified the genes encoding TORC1 complex subunits in the scallop Argopecten irradians irradians through genome-wide in silico scanning. Five genes, including TOR, RAPTOR, LST8, DEPTOR, and PRAS40, that encode the subunits of TORC1 complex were identified in the bay scallop. We then conducted structural characterization and phylogenetic analysis of the A. i. irradians TORC1 (AiTORC1) subunits to determine their structural features and evolutionary relationships. Next, we analyzed the spatiotemporal expressions of AiTORC1-coding genes during various embryo/larvae developmental stages and across different tissues in healthy adult scallops. The results revealed stage- and tissue-specific expression patterns, suggesting diverse roles in development and growth. Furthermore, the regulation of AiTORC1-coding genes was examined in temperature-sensitive tissues (the mantle, gill, hemocyte, and heart) of bay scallops exposed to high-temperature (32 °C) stress over different durations (0 h, 6 h, 12 h, 24 h, 3 d, 6 d, and 10 d). The expression of AiTORC1-coding genes was predominantly suppressed in the hemocyte but was generally activated in the mantle, gill, and heart, indicating a tissue-specific response to heat stress. Finally, functional validation was performed using the TOR inhibitor rapamycin to suppress AiTORC1, leading to an enhanced catabolism, a decreased antioxidant capacity, and a significant reduction in thermotolerance in bay scallops. Collectively, this study elucidates the presence, structural features, evolutional relationships, expression profiles, and roles in antioxidant capacity and metabolism regulation of AiTORC1 in the bay scallop, providing a preliminary understanding of its versatile functions in response to high-temperature challenges in marine mollusks.